Unravelling the structural plasticity of stretched DNA under torsional constraint - Graeme A. King (Nature Portfolio, 2016)
Cellular DNA is often torsionally constrained, but the topologies that such DNA can adopt under tensile strain have remained largely untested. Here, the authors use single-molecule optical tweezers to illustrate the structural plasticity of torsionally constrained DNA under mechanical force.